Usages récréatifs et agriculture en espace périurbain au nord de Nantes - Cécile Rialland-Juin (Projets de Paysage)
In a context of urban sprawl and airport project north of the city of Nantes, the implementation by authorities of a perimeter of protection of agricultural land and natural sparked conflicts over land use land opposing advocates of pursuing agricultural production targets to horse owners of plots motivated by leisure riding. The author examines the sources and analytical methods to measure, scale, unit, functions, challenges and opportunities of this recreational use only in agricultural and suburban areas north of Nantes.